Producción de energía eléctrica de la celda solar sensibilizada con colorante (DSSC) modificada: influencia del número de microceldas integradas - Bazán Galarreta, Elmo Fernando Manuel (2018)
The generation of electrical energy in solar cells sensitized with dyes (DSSC) modified in microcells was studied. A system of a 9.0 cm2 cell was designed, which was reduced in until areas cells of 2.25 cm2. The effect of the concentration of ZnO and TiO2 in the cells like semiconductors is studied and likewise, the effect of the concentration of anthocyanin in the generation of voltage and amperage. The cells were prepared in the catalysis laboratory of the National University of Trujillo. The results show that the concentration of anthocyanin does not influence cells impregnated with TiO2. The cells with TiO2 are the ones that generate the highest voltage and amperage. The highest voltage obtained is 1334 mV and the highest amperage obtained is 31.7 μA, in 16M cells of TiO2